Constitutive synthesis of tumor necrosis factor in the thymus. - Giroir, B P (1992)
Although tumor necrosis factor (TNF) is a major mediator of endotoxic shock, the normal function of TNF that has preserved this protein throughout mammalian evolution remains unknown. If the protein serves a role in normal development or homeostasis, it must be produced under physiologic conditions. To determine whether TNF secretion occurs in normal animals, and to define the tissue sources of the protein, we prepared a reporter construct in which the TNF coding sequence and introns are replaced by the chloramphenicol acetyltransferase (CAT) coding sequence. This construct was inserted into the murine genome, yielding 13 transgenic founders. Macrophages harvested from 4 of the transgenic lines expressed CAT activity after stimulation with Escherichia coli lipopolysaccharide in vitro. Each of these 4 transgenic lines also constitutively expressed CAT activity in the thymus but in no other tissue examined. Cultured thymocytes secrete TNF, as demonstrated both by cytotoxicity assays and by immunoprecipitation of radiolabeled thymic culture medium. CAT activity was associated with the thymic lymphocyte population and not with thymic macrophages or dendritic cells. CAT activity was present in thymic lymphocytes irrespective of CD4 or CD8 expression; T cells from the spleen, however, had no detectable CAT activity. The biosynthesis of TNF in the thymus of normal animals implies a role for this protein in the development or regulation of the immune response.